Sobre a formação de professores das séries iniciais na região de São José do Rio Preto-SP na ocasião dos Centros Específicos de Formação e Aperfeiçoamento para o Magistério (CEFAM) - Silva, Marinéia dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aimed at producing a historical narrative about the education of primary school teachers during the 1980's and 90's (at high-school level, as required then), in and around the city of São José do Rio Preto, State of São Paulo/Brazil. It approaches the profiles of teachers and students from different courses, political changes and continuities during the period, implemented proposals for teacher education, curricula, and teachers' personal experiences. This study is articulated with a broader one, conducted by GHOEM (Research Group on Oral History and Mathematics Education), which aims at producing a (historical) map of mathematics teacher education and practices in Brazil. Oral history was the chosen (qualitative) research methodology. We used available written sources and we constructed oral and written sources from interviews in order to compose a historical narrative on particular situations of the educational context in the state of São Paulo. We also dealt with the sequence of changes that took primary teacher education from Magistério through Normal School, Specific Habilitation within Pedagogy courses and, particularly, to the CEFAM's (implemented in 1988 and discontinued in 2005). We have also produced some information on (somewhat subtle) differences between current teacher education courses, as well as their institutions

Constituir uma narrativa histórica sobre a formação (em nível de 2° grau) de professores das séries iniciais na região de São José do Rio Preto/SP nas cercanias das décadas de 1980 e 1990 foi o objetivo desta pesquisa. Ela aborda perfis de docentes e discentes dos diferentes cursos de formação, (des)continuidades políticas, propostas implantadas, quadros curriculares e vivências de professores no período. Trata-se de uma colaboração com um dos projetos do Grupo de Pesquisa História Oral e Educação Matemática (GHOEM), cujo objetivo é elaborar um mapeamento (histórico) sobre a formação e atuação dos professores de Matemática no Brasil. Com um caráter qualitativo, a metodologia adotada nesta pesquisa é a História Oral. Utilizamos fontes escritas disponíveis e constituímos fontes orais e escritas a partir de entrevistas para compor uma narrativa histórica das situações particulares do contexto educacional paulista. Tratamos da transitoriedade dos cursos de Magistério, Normal, Habilitação Específica para o Magistério (HEM), e, sobretudo, do Centro Específico de Formação e Aperfeiçoamento para o Magistério (CEFAM), política educacional implantada no ano de 1988 e extinta em 2005 em todo o Estado de São Paulo e, consequentemente, na região pesquisada. A pesquisa ainda traz informações sobre as nuances que povoam os cursos superiores de formação de professores na atualidade, bem como suas instituições formadoras
Keywords: Centro Especifico de Formação e Aperfeiçoamento do Magisterio (SP); Mathematics - History; Matemática - História; Matemática - Estudo e ensino; Historia oral; Professores - Formação - Narrativas pessoais; Historiografia; São Jose do Rio Preto (SP)